A Qualitative Study of Online Media Narratives on The Primary Service Integration Program in Indonesia in 2024 - Rahayu, Eka Putri; Ariyanti, Rea (Universitas Mulawarman, 2025)
There is a new regulation in bringing health services closer to the community, namely Primary Service Integration (ILP), which is an important part of the transformation of the health system in primary care initiated by the Ministry of Health. This study was a qualitative study of online news portal content that aims to explain ILP policy in Indonesia. The research sample consists of national online media news about ILP policy published between January and June 2024. The researcher used the keyword ‘ILP’ and searched two online news portals. MAXQDA software was also used as a data analysis tool in this study. Features used included Word Cloud and word frequency to understand the main concepts. The results showed that there were four dominant topics in the coverage of well-known online media in Indonesia related to ILP policy in Indonesia. The topic of expectations related to ILP was the most dominant topic with 12 quotes